Učenje kolesarjenja v predšolskem obdobju - Videmšek, Mateja (Šport (Ljubljana), 2019)
The article introduces learning of cycling for children in the pre-school period. A tool that perfectly prepares a child to learn to ride a real bike is the balance bike. It significantly changed the learning of cycling that we were used to in the past. The article describes what we need to pay attention to when buying a balance bike, how to approach children%s learning of cycling with a balance bike, and how a child can easily upgrade to the right bike after using a balance bike. Children have an easier time learning how to ride a bike when starting with a balance bike because it is done through a play so that a child has fun and learns new skills at the same time. A child thus enjoys learning progress and thereby gains a positive attitude towards cycling.
Keywords: balance bike; cycling; kolesarjenje; malčki; poganjalec; predšolski otroci; preschool children; sport; šport; toddlers